Perancangan Sistem Deteksi Dini Lift Barang Berbasis Arduino di PT Dharma Electrindo Manufacturing - Maharani Ongky Anggraini; Antonius Suhartomo (President University, 2019)
PT Dharma Electrindo Manufacturing is one of the compant in automotive manufacture. This company has two plants which are in Cikarang and Cirebon, with Cirebon focusing on the manufacturing side. PT Dharma Electrindo Manufacturing Cirebon branch has three floors for production. Thus it is necessary to have a freight elevator to ease production process on second and third floor with support from AGV (Automatic Guided Vehicle) with the market price of Rp 200.000.000 without humans directly controlling it. Several accidents could happen due to unsynchronized elevator door and AGV. In 2017, 15 accidents occurred on the elevator door on the second floor. Because of this, an early detection system has been implemented in the form of a crossbar on the door such that the AGV does not hit the acrelyte-made door which could cause the AGV to fall and caused the company loss about Rp 200.000.000 or the broken elevator door all through 2017 which caused Rp 202.250.000 loss. It is hoped that this crossbar implementation is developed using stabilizer.